Morphometric characterization of Katjang goat of Malaysia (Bangladesh Journal of Animal Science, 2017)
Morphometric characterization of Katjang goat in Malaysia is important for conservation and for further genetic improvement. With this idea in view the present study was carried out to characterize the morphometry and to estimate the relationship among the important morphometric traits of indigenous Katjang goat. The study was conducted at the Faculty of Sustainable Agriculture (FSA), surrounding area of FSA Sandakan, Sabah and Batu Pahat, Johor in Malaysia. Characteristics of body weight (BW), body length (BL), heart girth (HG), wither height (WH), hip height (HH), fore leg length (FLL), hind leg length (HLL), head length (HeL), head width (HW), ear length(EL), ear breadth (EB), tail length (TL), scrotal length (SL) and scrotal circumference (SC) were gathered. In a single parameter as body weight of Katjang bucks at below 1 year, 1-2 year and > 2 years ages were recorded to be 7.41 ± 0.27, 14.20±0.20 and25.83 ± 0.99 kg, respectively. On the hand, body weight of Katjang does at 1-2 year and > 2 years ages were observed to be 12.41 ± 0.41 and 23.65±0.87 kg, respectively. In both sexes, head length, head width, tail length, ear length, ear breath, body weight, body length, hearth girth, wither height, leg length, hip height increases with the increment of the age of goat. On the other hand, all the parameters contemplated found comparatively higher in bucks than that of does.  Strong positive correlation was observed between scrotal length and scrotal circumference in Katjang bucks.Bang. J. Anim. Sci. 2016. 45 (3): 17-24